Hospitalization dynamics during COVID-19: Insights into disease trends and patient outcomes - Mahsa Motiei; Afagh Hassanzadeh Rad; Hamidreza Badeli; Reza Bayat (PLoS ONE, 2025)
Objectives To find the pattern of hospitalization pattern change in COVID-19 pandemic, we aimed to compare the admission and mortality rate of each disease in all wards before and during the pandemic. Methods Data for all ICD-10 disease categories were collected from 17 shahrivar hospital database for 14922 patients before (23 July 2017–23 January 2020 (and 10941 patients during the pandemic (20 February 2020- 20 September 2022). We compared the age, sex, duration of hospitalization, the frequency of readmission and outcome of patients in these two periords. Also the number of patients in each ICD-10 category and in each ward was compared. Results Comparing the two periods revealed a decrease in overall admission frequency (14,922 vs. 10,941 patients). During the pandemic, patients experienced significantly shorter hospital stays (P < 0.001). There was no significant difference in the number of patients entering remission or experiencing mortality (P = 0.063). Notably, admissions for neoplasms, blood disorders, nervous system conditions, eye disorders, circulatory and digestive system issues, genitourinary system disorders, congenital malformations, and poisoning significantly increased during the pandemic, while admissions for other conditions decreased. Admissions varied significantly across departments, with notable increases in the NICU, PICU, emergency, neonatal, and hematology departments during the pandemic (P < 0.001). Conclusions In conclusion, our findings highlight the impact of the COVID-19 pandemic on hospitalization patterns, equipping healthcare managers to improve resource allocation and readiness for future health challenges.